Injectable Microannealed Porous Scaffold for Articular Cartilage Regeneration. (June 2020) - Schaeffer, Christine; Pfaff, Blaise N.; Cornell, Nicholas J.; Salopek, Lisa S.; Shan, Sarah; Viyar, Jan; Omesiete, Wilson; Griffin, Donald R.; Cottler, Patrick S.; DeGeorge, Brent R.
Abstract : Background: The purpose of this study is to assess the feasibility of a novel microporous annealed particle (MAP) scaffolding hydrogel to enable both articular cartilage and subchondral bone biointegration and chondrocyte regeneration in a rat knee osteochondral defect model. Methods: An injectable, microporous scaffold was engineered and modified to match the mechanical properties of articular cartilage. Two experimental groups were utilized—negative saline control and MAP gel treatment group. Saline and MAP gel were injected into osteochondral defects created in the knees of Sprague-Dawley rats. Photo-annealing of the MAP gel was performed. Qualitative histologic and immunohistochemical analysis was performed of the treated defects at 2, 4, and 8 weeks postsurgery. Results: The injectable MAP gel successfully annealed and was sustained within the osteochondral defect at each timepoint. Treatment with MAP gel resulted in maintained size of the osteochondral defect with evidence of tissue ingrowth and increased glycosaminoglycan production, whereas the control defects presented with evidence of disorganized scar tissue. Additionally, there was no significant inflammatory response to the MAP gel noted on histology. Conclusions: We have demonstrated the successful delivery of an injectable, flowable MAP gel scaffold into a rat knee osteochondral defect with subsequent annealing and stable integration into the healing wound. The flowable nature of this scaffold allows for minimally invasive application, for example, via an arthroscopic approach for management of wrist arthritis. The MAP gel was noted to fill the osteochondral defect and maintain the defect dimensions and provide a continuous and smooth surface for cartilage regeneration, suggesting its ability to provide a stable scaffold for tissue ingrowth. Future chemical, mechanical, and biological gel modifications may improve objective evidence of cartilage regeneration.